2014
DOI: 10.1155/2014/242180
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Steen Solution Properties: Breakthrough in Antioxidant Effects via NOX2 Downregulation

Abstract: Ex vivo lung perfusion (EVLP) allows perfusion and reconditioning of retrieved lungs for organ transplantation. The Steen solution is specifically designed for this procedure but the mechanism through which it elicits its activity is still to be fully clarified. We speculated that Steen solution may encompass antioxidant properties allowing a reestablishment of pulmonary tissue homeostasis. Blood samples from 10 healthy volunteers were recruited. Platelets and white cells were incubated with Steen solution or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 18 publications
2
20
0
2
Order By: Relevance
“…Among them, H 2 O 2 is one of the most abundant and stable molecules in vivo for reliable quantification. Decreasing detrimental ROS production during IRI has been previously proposed as a strategy for improving LTx; our recent contribution (6) and the present study further support this approach, evidencing for the first time the antioxidant properties of Steen solution on parenchymal cells through the downregulation of NOX activity, in particular of NOX2 isoform. Our results consistently showed that ROS levels were significantly increased after CS/NR, and reduced by Steen solution in all cell types, indicating its protective effects during EVLP also by reducing IRI.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Among them, H 2 O 2 is one of the most abundant and stable molecules in vivo for reliable quantification. Decreasing detrimental ROS production during IRI has been previously proposed as a strategy for improving LTx; our recent contribution (6) and the present study further support this approach, evidencing for the first time the antioxidant properties of Steen solution on parenchymal cells through the downregulation of NOX activity, in particular of NOX2 isoform. Our results consistently showed that ROS levels were significantly increased after CS/NR, and reduced by Steen solution in all cell types, indicating its protective effects during EVLP also by reducing IRI.…”
Section: Discussionsupporting
confidence: 82%
“…Considering our previous results on immune cells (6), and since epithelial cell injury and endothelial dysfunction are among the main pathogenetic events of primary graft dysfunction (PGD) (12), we hypothesized that the antioxidant properties of the Steen solution may be responsible for cytoprotective effects on parenchymal (epithelial, LPCs) and endothelial cells, sustaining the response to lung damage and/or regeneration. Thus, we investigated the effects of the Steen solution and cell-type specific mechanisms on PSs, made of epithelial/basal cells and LPCs, and on the endothelial cell line human umbilical vein endothelial cells (HUVEC), subjected to in vitro cold starvation followed by normothermic recovery, providing novel significant insights on the beneficial effects of Steen solution on parenchymal cell types.…”
Section: Introductionmentioning
confidence: 99%
“…The inflammatory profile reveals a major reduction in cytokine expression in lungs from the EVLP group compared to both in vivo Control and ex vivo Control, suggesting a ‘resetting’ of the inflammatory milieu(13, 14). The clinical implications of these changes in inflammatory signaling are not completely clear.…”
Section: Commentmentioning
confidence: 98%
“…EVLP reduces LIRI and may attenuate the oxidative stress response that is generated during brain death and ICU-related complications when compared to standard cold-ischemic storage. There is evidence that the perfusion solution developed by Steen et al may provide antioxidant protection by inhibiting NOX2 activation in the donor lung during lung perfusion (89).…”
Section: Perfusion Liquidsmentioning
confidence: 99%